Effect of bicarbonate and progesterone on plasma membrane integrity, acrosome reaction and proportion of fatty acids in boar sperm - Choon-Keun Park; Sang-Hee Lee (The Korean Society of Animal Reproduction and Biotechnology, 2022)
This study investigated the influence of sodium bicarbonate (NaHCO3) and progesterone on acrosome reaction and proportion of polyunsaturated fatty acid (PUFA) composition boar sperm. The sperm were diluted with semen extender and incubated with NaHCO3 and progesterone at 38℃, 5% CO2 for 6 h. Plasma membrane integrity and acrosome reaction were analyzed using SYBR14/propidium iodide (PI) and FITC-PNA/PI doubling staining method, and proportion of PUFA was analyzed using gas chromatography. In results, Plasma membrane integrity was significantly decreased in 50 mM NaHCO3 group and acrosome reaction was significantly increased by over the 100 mM NaHCO3 group compared to control group (p < 0.05). In addition, progesterone significantly increased decreased plasma membrane integrity at 100 mM progesterone and acrosome reaction at over the 5.0 µM progesterone (p < 0.05), but there was no difference among the 5.0 to 100 µM groups. PUFAs were significantly decreased in 100 mM NaHCO3 and 50 µM progesterone treatments compared to control group. In summary NaHCO3 and progesterone induce acrosome reaction and reduce PUFA composition in boar sperm, therefore, the results maybe help to understand basically knowledge for the acrosome reaction and PUFA composition in boar sperm.